(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
نفذ البحث خلال الموسمين الزراعيين 2002-2004 في المنطقة الساحلية السورية(طرطوس) على أربعة أصناف مدخلة من الفول Vicia faba , استخدم الصنف البلدي شاهد. بينت نتائج البحث وجود تأثيرات معنوية بين صفات الأصناف المدروسة. تفوق الصنف ايكاروس بالإنتاجية البذرية على باقي الأصناف والشاهد حيث بلغت 1120 غ/م2 إضافة لتفوقه بمعظم الصفات المدروسة, يليه الصنف F90 983 غ/م2 من البذور إضافة لتبكيره في النضج( 137 يوماً) . من خلال نتائج الدراسة يعتبر الصنفان ايكاروس وF90 هامين زراعياً في المنطقة الساحلية السورية والمناطق المشابهة, فضلاً عن استخدامهما كأصول وراثية للصفات التي تفوقا بها على بقية الأصناف. This research was conducted during 2002-2004 in the costal region of Syria (Tartous) on the five varieties of the horse bean. The local variety was used as a control. The study showed significant differences among varieties with regard to the traits under investigation, variety Ecaros was supeior in terms of seed production, seed weight/ plant, the number of seeds 1120g2 /pod the number of pods/ plants and the length of pod). Varity F90 ranked 983g2 second in terms of productivity elements (137 days). We can conclude that these two varieties Ecaros, (F90) were fairly efficient in the region of study.